Harga dan Kenyamanan Pelayanan : Apakah Berpengaruh Terhadap Minat Beli Pengguna KAI Access? - Laila Fitri Nur Zahrani; Yasinta Ayu Dewantari; Faiqotul Ilmiyah; Khairani Zikrinawati; Zulfa Fahmy (Student Research Journal, 2023)
Purchase intention is an important factor for users in using the KAI Access transportation service because user buying interest will automatically appear when the user is sure and trusts and feels interested in the goods (services) being offered. The purpose of this study was to determine the effect of price and service convenience on the buying interest of KAI Access users. This study uses KAI Access users as a population, and KAI Access users who are domiciled in Semarang as a sample. This research is a quantitative research using a non-experimental research design. Purposive sampling is sampling according to what is desired as a sampling method in this study. The data collection technique by distributing price questionnaires and the questionnaire used is the service convenience scale consisting of 13 items and the buying interest scale consisting of 13 items. The scale is presented using a Likert scale in intervals of 1-5 and questionnaires in intervals of 0-1 with a sample of 107. In this study, multiple linear regression analysis was used for the data analysis technique. In addition, hypothesis testing uses hypothesis testing (t-test), feasibility test (f-test), validity, reliability and normality, using the SPSS software. This study resulted in a statement that the price hypothesis has no significant effect on the purchase intention of KAI Access users. Meanwhile, service convenience has been empirically proven to have a significant effect on the purchase intention of KAI Access users. An important finding in this study is that there is no effect of price on the buying interest of KAI Access users.